Antimicrobial defense of the earthworm - Bilej, M; De Baetselier, P; Beschin, A (Folia microbiologica, 2000)
Discrimination of self and nonself is one of the features of all animal species but the ways of elimination of nonself are different. Defense strategies of invertebrates, which lack antibodies and lymphocytes, are based on innate defense mechanisms. The study of such, undoubtedly less complex, defense mechanisms in invertebrates may shed a new light on the more sophisticated immunity of vertebrates. The main aim of this review is to show on one experimental model--an oligochaete annelid--cellular and humoral defense pathways protecting against microbial infection.
Keywords: lektiny; Oligochaeta; proteiny; prezentace antigenu; hemolyziny; biologické toxiny; molekulární sekvence - údaje; Amino Acid Sequence; Cytotoxins; sekvenční seřazení; Animals; Toxins, Biological; Lectins; zvířata; sekvence aminokyselin; Molecular Sequence Data; Antigen Presentation; Hemolysin Proteins; Proteins; cytotoxiny; Sequence Alignment